The oldest Ordovician foraminifers (Oepikodus evae conodont Zone, Floian) from South America - Nestell, Galina; Heredia, Susana Emma; Mestre, Ana; Beresi, Matilde Sylvia; González, Mercedes (Geobios)
The oldest occurrences of the monothalamous foraminifer species. Amphitremoida longa Nestell and Tolmacheva and A. laevis Nestell and Tolmacheva are found in the San Juan Formation together with conodonts of the Oepikodus evae Zone of the Floian (Lower Ordovician), in the Salagasta 2 section, southern Precordillera, Argentina. These discoveries represent the oldest record for foraminifers in South America. The foraminifers, species of which were originally described from the Lower Ordovician of northwestern Russia, are found in shallow high energy carbonate platform deposits in the Precordillera, together with a North Atlantic province conodont fauna. The carbonate sequence of the San Juan Formation in the Salagasta region is interpreted as a succession ranging from shallower tidal deposits to carbonate crinoidal shoaling bar deposits. Fil: Nestell, Galina. The University Of Texas At Arlington; Estados Unidos. Saint Petersburg State University; Rusia Fil: Heredia, Susana Emma. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Mestre, Ana. Universidad Nacional de San Juan. Facultad de Ingeniería. Instituto de Investigaciones Mineras; Argentina Fil: Beresi, Matilde Sylvia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza; Argentina Fil: González, Mercedes. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Regional de Investigaciones Cientifícas y Tecnológicas; Argentina